Analysis Of The Effect Of Work Environment And Intrinsic Motivation On Performance Of Employees Sushi TEI Tunjungan Plaza Surabaya - Bunga Erika Putri; Hermien Tridayanti (Journal of World Conference (JWC), 2020)
The purpose of this study is to find out and analyze the work environment and intrinsic motivation significantly simultaneously on the performance of Sushi Tei Tunjungan Plaza Surabaya employees. With a population of 85 respondents. This research is quantitative and data collection is through questionnaires and observations. Data analysis used is validity test, reliability test, classic assumption test, multiple linear analysis test. The results showed that the analysis of the influence of the work environment and intrinsic motivation on the performance of employees at Tunjungan Plaza Surabaya Sushi Tei on the results of the t test of the work environment wascalculated as -4.971 <Ttable 1.666 and intrinsic motivation of Tcount 13.189> Ttable 1.666. For the results of the F test it is known that Fcount 110,267> Ftable 3.11, it can be concluded that environmental variables and intrinsic motivation have ainfluence simultaneouson employee performance